Pahorjeva Nekropola - Paternu, Boris (Jezik in slovstvo, 2014)
The key existential question of Pahor's novel Necropolis (1967) is that of man surviving terrible violence, surviving in "a world of the ultimate negation". There are a number of positions of power within powerlessness, from an identification fully adjusted to the given reality, including a conscious exclusion of all other thoughts and emotions and exits from "mere existence", to the resistant mental reflexes of the primeval social ethos, humanism or political stability. It is a case of the different levels of resisting "moral intelligence" (Georg Steiner). However, the innermost virus of "resilience" in Pahor is located neither in ideology nor in philosophy, but in his unspoilt love of life and in a defiance that was made even more determined by fascism with its genocidal policy towards Slovenes. Pahor's novel has a style structure that is multifaceted and dynamic. It deviates significantly from labour-camp verism or "suprarealism" (Levi's concept), displaying a preference for a narrative of metaphors, personal expression and the surreal. This narrative is a fusion of personal testimony realism and strongly imaginative narration; it is, in a sense, a conjunction of a document and poetry. The spiritual and stylistic blueprint of Necropolis becomes even more distinct when positioned next to Primo Levi and Imre Kertész, or even Dostojevsky, as a kind of pioneer of the labour-camp novel. Pahor takes the labour-camp novel on a completely new, specific path, perhaps a Slovenian path. The tradition of symbolism and expressionism has been rather strong in Slovenian literature. Pahor chose a motto by Srečko Kosovel for the novel.
Keywords: Pahor, Boris, 1913-; "Nekropola"; Slovene literature; slovenska književnost; slovenska zamejska književnost; taboriščni roman; realizem; nadrealizem; Surrealism